Modelling of Welded Joint Geometry in Sheet Metal Welding; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Pavlov N. V. Nikolay Viktorovich; Kryukov A. V. Artem Viktorovich; Zernin E. A. Evgeny Aleksandrovich; Polischuk V. A. (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen